Single-Laboratory Validation Study of Rapid Analysis Method for Multi-Class Veterinary Drugs in Milk, Fish and Shellfish by LC-MS/MS - TATEISHI, Yukinari; HASHIMOTO, Tsuneo; MATSUSHIMA, Yoko; TAKANO, Ichiro; NAGANO, Chieko; KANDA, Maki; HAYASHI, Hiroshi; KANAI, Setsuko; SASAMOTO, Takeo; NAKAJIMA, Takayuki (Food Hygiene and Safety Science (Shokuhin Eiseigaku Zasshi), 2013)
A method of rapid analysis of multi-class residual veterinary drugs in milk, fish and shellfish was validated in accordance with Japanese guidelines for the validation of analytical methods for residual agricultural chemicals in food. Using LC-MS/MS, 43 multi-class veterinary drugs, including sulfonamides, quinolones, coccidiostats and antiparasites, could be analyzed in one injection. Analytes were extracted from samples with two kinds of solvent, acetonitrile containing 1 vol% formic acid and anhydrous acetonitrile, and salted out with 4.0 g of magnesium sulfate, 1.5 g of trisodium citrate and 2.0 g of sodium chloride. This method was assessed by performing recovery tests in retail milk and 4 kinds of fresh cultured fish and shellfish (salmon, tiger shrimp, red sea bream and bastard halibut) spiked with the 43 target analytes at the levels of 10 and 100 μg/kg. Using this method, 40 out of 43 drugs satisfied the guideline criteria in milk, 37 drugs in salmon, 42 drugs in tiger shrimp, 41 drugs in red sea bream and 39 drugs in bastard halibut.